EU-induced Financialisation and Its Impact on the Greek Wage Share, 1999-2021 - Giorgos Gouzoulis; Panagiotis Iliopoulos; Giorgos Galanis (Global Labor Organization (GLO), 2022)
This paper examines the determinants of the income share of wage earners in the non-financial, private sectors of Greece since its introduction to the Eurozone in 1999. The main outcome of the integration of Greece into the Eurozone has been the financialisation of its economy, which has been particularly influential for households since it led to the rapid rise of household indebtedness. Building on recent research within industrial relations, sociology of work, and political economy, which shows that financialisation is a key driver of wage bargaining outcomes, we demonstrate that the relative size of the FIRE sectors and the increase in household debt have been negative drivers of the wage share in Greece over the last 22 years. Our findings also suggest that the employment-tied social benefits system and tertiary education provision have also been important determinants of workers' income share.
Keywords: E24; E25; D33; F36; G51; 330; Financialisation; Household Debt; EU Integration; Wage Share; Greece